2016
DOI: 10.1007/s10103-016-1989-5
|View full text |Cite
|
Sign up to set email alerts
|

Lower face lifting and contouring with a novel internal real-time thermosensing monopolar radiofrequency

Abstract: As demand for a youthful appearance has increased, various techniques for face lifting and contouring have been used to reduce excess fat deposition and improve skin laxity. Recently, radiofrequency (RF)-assisted lipolysis and liposuction (RFAL) has been introduced for body and face contouring. This study aimed to evaluate the clinical improvement and safety of a new RFAL device for face lifting and contouring. A prospective study was conducted in 20 Korean patients who underwent an internal real-time thermose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…3 Patient CD, age 58, before the first session of treatment with non-ablative RF and after the last one Fig. 4 Patient EF, age 43, before the first session of treatment with intense pulsed light session and after the last one insignificant [3]. Shin et al used R2 and R5 parameters to evaluation of IPL application in a group of 23 women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Patient CD, age 58, before the first session of treatment with non-ablative RF and after the last one Fig. 4 Patient EF, age 43, before the first session of treatment with intense pulsed light session and after the last one insignificant [3]. Shin et al used R2 and R5 parameters to evaluation of IPL application in a group of 23 women.…”
Section: Discussionmentioning
confidence: 99%
“…Cutometric measurement showed significant changes in the following parameters: elasticity (R2 + 5.9%), viscoelasticity (R8 − 9.4%), fatigue (R3 and R9 − 16.2%, − 19.7%, respectively) and thickness R0 − 14.9%) [ 2 ]. Kim et al conducted a Cutometer study to assess the effect of monopolar radiofrequency treatment on skin elasticity; however, their results were statistically insignificant [ 3 ]. Shin et al used R2 and R5 parameters to evaluation of IPL application in a group of 23 women.…”
Section: Discussionmentioning
confidence: 99%
“…48 For elasticity, a study on patients who underwent monopolar RF-assisted lipolysis (RFAL) measured improvement in elasticity at buccal and submental areas (upward trend at 12 vs. 24 weeks) by cutometer although not statistically significant (n = 20). 63 Another study on 44 patients treated with fractional RF found elastometry measurements with significant improvement (5%-12% in Young's Modulus and 10%-16% decrease in retraction time, p < 0.05). Average elasticity improvement correlated to a 2.6-year enhancement in skin property.…”
Section: Retrospective Studymentioning
confidence: 95%
“…Sixty percent of RF patients were satisfied and 33% were very satisfied. 34 Similar to RF of the facial upper third, studies in the lower face show rhytid reduction 54,59,60 and improved skin laxity, 32,33,49,54,59,[61][62][63] but no difference in TEWL. 48 For elasticity, a study on patients who underwent monopolar RF-assisted lipolysis (RFAL) measured improvement in elasticity at buccal and submental areas (upward trend at 12 vs. 24 weeks) by cutometer although not statistically significant (n = 20).…”
Section: Retrospective Studymentioning
confidence: 99%
See 1 more Smart Citation